Сабақ үдерісінде жаңа технология əдістерін қолданудың маңыздылығы - Аманбаева, А.Ш. (My University, 2016)
The article emphasizes the importance of translation of experience of the Nazarbayev University and "Nazarbayev Intellectual Schools" Kazakhstan's education system. Have shown the effectiveness of constructive learning in high school, is the most significant among the various theoretical foundations of Cambridge teaching methods to achieve high learning outcomes in the world. The main direction of this method lies in the development of the thinking of students.
Keywords: Cambridge teaching methods; general secondary obrazovanie constructive training.